Projakościowa kultura organizacyjna w przedsiębiorstwa przemysłu stoczniowego - Dajczak, Katarzyna (The Organizational Culture of Quality in Enterprises of Shipbuilding Industry, 2008)
The current economic reality extorts on enterprises continuous work over building the competitive superiority. The organizational culture becomes the common ground of searches for this superiority. The future of management rests in its development. The organizational culture is the basis of identity of a firm and its suitable image in customers' eyes, determination of success... And therefore, it is necessary to shape the organizational culture consciously because it marks the frame of behaviours and conditions of decisions undertaken by all members of organization, decides about its efficiency and competitiveness. From here, the culture of quality gathers special weight, which favours the general quality, unites the workers in one community, steers their workings and commitment in realization of aim of organization - improvement quality, and the enterprises of shipbuilding industry are this example. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 295-304